Interest rate risk in Kenya: The banking sector stability and fiscal risks nexus - Camilla Talam; Samuel Kiemo (Kenya Bankers Association (KBA), 2024)
The study sought to examine the effect interest rate risks on banking sector stability through disentangling the effect of interest rate risk on both fiscal and banking sector stability conditions in Kenya. We applied annual macroeconomic and bank-level data for the period 2001 - 2022 across 37 banks. The study also developed a banking sector stability index to examine evolution of banking sector stability , undertook sensitivity analysis on interest rate sensitive assets k and applied panel fixed effects model to examine the effect of interest rate and fiscal policy risks on banking sector stability . The study found that overall, the banking sector has remained resilient over the study periods, despite experiencing some periods of financial instability. The study also found monetary policy stance has implications on fiscal and banking sector stability whereby contractionary monetary policy raises fiscal and banking sector stability risks when public debt is elevated due to a tight sovereign-bank nexus. Increases in interest rate and credit risks were found to lower banking sector stability while bank capital accumulation strengthened banking sector stability . A high sovereign-bank nexus increases banking sector stability through repricing risks reflected via interest rate and liquidity risks. On other hand banks' portfolio diversification and trading strategies help to mitigate and lower repricing risks from market and interest rate changes. The paper proposes tracking of sovereign-bank nexus overtime to cover multiple business cycles to enhance understanding of sovereign-bank nexus dynamics towards coordinating monetary, fiscal and macroprudential policies.
Keywords: 330; Banking sector stability; Fiscal Risks; Monetary policy